Conversor Push-Pull modificado baseado na célula de comutação de três estados - Ferreira, Daniel Lima (2010)
This work presents the steady state study of a modified DC-DC Push-Pull converter obtained from the DC-DC Boost converter based on Three State Switching Cell (TSSC). For the converter a qualitative and quantitative analysis was made operating in all duty cycle variation (0≤ D ≤1). Such analysis was realized in continuous conduction mode CCM, and in discontinuous conduction mode DCM. The topological modification relative to the classical DC-DC push-pull converter, it permits only one primary winding utilization in the isolated high frequency transformer. The presence of one primary winding it facilitates the series capacitor connection to avoid direct-current circulation, so, prevents the isolated high frequency transformer saturation. To verify its feasibility a prototype with 48VDC input voltage, 400VDC output voltage, and 2kW output power was assembled.